2019
DOI: 10.7201/earn.2019.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Using mixed research approaches to understand rural depopulation

Abstract: <span lang="EN-US">There is a growing consensus on the need to propose specific policies to face rural depopulation. This article applies fuzzy-set Qualitative Comparative Analysis (QCA) to define the presence or absence in each municipality of the conditions leading to the presence or absence of depopulation. We also perform Exploratory Spatial Data Analysis (ESDA) of population growth to identify hotspots of rural depopulation. The methodologies prove useful to evaluate and guide regional policies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…Chi (2012) also found that in rural areas of Wisconsin highway improvement promotes population growth. A similar result was obtained by Alamá-Sabater et al (2019), who study the factors that condition rural depopulation using data at the municipality level in Valencia, finding that lack of accessibility of rural locations is a sufficient condition for high depopulation risk.…”
Section: Estimation and Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Chi (2012) also found that in rural areas of Wisconsin highway improvement promotes population growth. A similar result was obtained by Alamá-Sabater et al (2019), who study the factors that condition rural depopulation using data at the municipality level in Valencia, finding that lack of accessibility of rural locations is a sufficient condition for high depopulation risk.…”
Section: Estimation and Resultssupporting
confidence: 80%
“…The per capita income-gap with urban areas, the growth of the working population, and the aging rate in rural areas appear to be the main drivers of rural depopulation. Alamá-Sabater et al (2019) study the factors that affect rural depopulation using data at the municipality level from the Spanish region of Valencia. They assess the conditions for a location being potentially at high risk of depopulation, finding that low accessibility is a sufficient condition for high depopulation risk.…”
Section: Explaining Rural Depopulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 84 , 86 , 88 , 89 , 91 , 94 , 95 , 97 , 99 , [101] , [102] , [103] , 105 , 107 , 109 , 112 ], to Refs. [ 114 , [116] , [117] , [118] , [119] , 125 , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , 139 , [141] , [142] , [143] ]; it is followed by that of Responsible production and consumption (12) who study it in Refs. [ 85 , 89 , 94 , [98] , [99] , [100] , [101] , [103] , [104] , [105] , 107 , 117 , 119 , 120 , [122] , [123] , [124] , [125] , [126] , [131] , [132] , [133] , [134] , [135] , 141 , 144 ]; also that of Decent work and economic growth (8) where its main aspects are worked on in Refs.…”
Section: Discussionmentioning
confidence: 99%
“…En los últimos años han adquirido una mayor importancia los estudios que buscan paliar o mitigar los desequilibrios territoriales subyacentes en diferentes enclaves espaciales, localizados a lo largo y ancho de nuestro mundo, que se abordan desde múltiples escalas de análisis. En concreto, destacan aquellas investigaciones que se centran en exponer las dificultades de ciertas zonas, como acontece por ejemplo en los entornos rurales, para disponer de unas oportunidades de desarrollo socioeconómico equitativas que les permitan contener el proceso de pérdida progresiva de efectivos poblacionales y, a su vez, reforzar las iniciativas o acciones dirigidas a la fijación de la población en estos espacios (Alamá-Sabater et al, 2019).…”
Section: Introductionunclassified